2014
DOI: 10.3171/2013.9.jns13877
|View full text |Cite
|
Sign up to set email alerts
|

Gross-total resection outcomes in an elderly population with glioblastoma: a SEER-based analysis

Abstract: Object There is limited information on the relationship between patient age and the clinical benefit of resection in patients with glioblastoma. The purpose of this study was to use a population-based database to determine whether patient age influences the frequency that gross-total resection (GTR) is performed, and also whether GTR is associated with survival difference in different age groups. Methods The authors identified 20,705 adult patients with glioblastoma in the Surveillance, Epidemiology, and End … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
1
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(83 citation statements)
references
References 23 publications
3
74
1
5
Order By: Relevance
“…Furthermore, we defined ''extent of resection'' based on the surgical codes provided by SEER that are most in keeping with GTR (i.e., ''Radical, total, gross resection'', ''resection of lobe of brain'', ''Gross total resection of lobe of brain''), and STR (i.e., ''Local excision'', ''excisional biopsy'', or, ''Subtotal resection''). This is consistent with previous work by ourselves [35] and others [41]. However, SEER does not offer a standardized or recommended means of defining these variables.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, we defined ''extent of resection'' based on the surgical codes provided by SEER that are most in keeping with GTR (i.e., ''Radical, total, gross resection'', ''resection of lobe of brain'', ''Gross total resection of lobe of brain''), and STR (i.e., ''Local excision'', ''excisional biopsy'', or, ''Subtotal resection''). This is consistent with previous work by ourselves [35] and others [41]. However, SEER does not offer a standardized or recommended means of defining these variables.…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, the survival times in that study (5.1 months for SRT and 5.6 months for HRT) were closer to the survival estimates of the patients in this analysis who were treated with alternatives to SRT. The relatively short survivals in the Roa study may be explained by the limited proportion of enrolled patients (<15%) who had undergone complete surgical resections, since the extent of surgery has been shown to positively affect survival (25). In addition, this trial was closed early due to slow accrual and was not sufficiently powered to conclude that the two treatments were truly statistically equivalent.…”
Section: Groups -----------------------------------------------------mentioning
confidence: 99%
“…A possible explanation for this discrepancy is that, in this population-based retrospective analysis, patients treated with these abbreviated therapies possibly had worse prognostic factors (i.e., extent of surgery and performance status) compared with the patients enrolled in the German NOA-08 and Nordic clinical trials. To clarify, although the extent of surgery was beyond the scope of this analysis, in 2014 Noorbakhsh et al (25) published a SEER-based population study of elderly GBM patients, analyzing the extent of resection and the outcomes. They found that, of the 3,631 patients aged ≥75 years, only 24.2% had undergone complete resection, 24.1% had undergone partial resection, 17.2% local excision or biopsy, 32.7% had received no surgery and 1.8% was unknown.…”
Section: Groups -----------------------------------------------------mentioning
confidence: 99%
“…The high rate of GTR in this cohort of elderly patients may also support this notion, because nationwide studies have shown older patients to receive GTR significantly less frequently than younger patients. 31 In addition, many patients in this study were enrolled in a variety of clinical trials, such as those evaluating combination therapies and immunotherapy. As a result, the varying treatment and follow-up protocols may have affected patient survival.…”
mentioning
confidence: 99%